ANALISIS FISIOLOGI JAMUR LIGNINOLITIK DAN SELULOLITIK ASAL TANAH GAMBUT DESA RIMBO PANJANG KABUPATEN KAMPAR SEBAGAI AGEN BIOKOMPOS - Karina Larasati; Rodesia Mustika Roza; Atria Martina (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cellulolytic and ligninolytic fungi have an important role in degradation of organic materials, especially lignin and cellulose, in a composting process. The success of the fungi in the composting process is strongly influenced by temperature and pH. The purpose of this research was to obtain isolates of the fungi with the best ability to be applied as biocompost agent by analyzing its ability to grow in different temperature and pH. A total of 110 isolates from peatsoil in Rimbo Panjang, Kampar Regency, Riau was inoculated into Potato Dextrose Broth medium with pH of 5 and pH of 7 then incubated for 3 days at room temperature (±27ºC), 40ºC, 50ºC, 60°C, 70ºC and 80ºC. The results obtained 110 isolates which were grown at room temperature (±27ºC) with pH of 5 and pH of 7 and 96 isolates which were grown at 40ºC temperature. A total of 27 isolates which were grown at 50ºC temperature consisted of genus Penicillium, Trichoderma, and Aspergillus.